Design and Construction of a Bedroom Monitoring Device for the Elderly Using LoRa Communication and the Internet of Things - Muhammad Anshory; Tamaji; Erwin Dhaniswara (Journal of Creative Power and Ambition (JCPA), 2026)
The elderly are a group of people experiencing declining physical health and mobility. According to various studies, they are at risk of health problems such as falls in their bedrooms, unstable body pressure, sleep disturbances, and even medical emergencies. The Internet of Things (IoT) implements a more responsive, accurate, and ubiquitous health monitoring system, such as LoRa (Long Range), a low-power, wide-range wireless communication system that can be used to efficiently transmit sensor data remotely. The design consists of two boxes: one as a transmitter and the other as a receiver. Both the receiver and transmitter use a Wemos D1 R32 and LoRA RA-02 with antennas. The transmitter sends data in the form of temperature and humidity, which are read by the DHT-11, and noise by the MAX4466 and a button. The data is sent and received by the receiver module, which displays it on the LCD and activates a buzzer with a telegram notification. Tests showed that the device can read temperature and humidity, detect noise, and send a panic button signal. It displays data on the LCD, activates a buzzer, and sends telegram notifications in the event of an alert. Wireless transmission utilizes the LoRa RA-02 module for communication between the transmitter and receiver modules.